Global committments to youth rights : a guide for young people to the government agreements from the UN world conferences from Rio to Istanbul - Humble, Morag (Commonwealth Secretariat LondonGB, 1997)
Provides a guide to the major world conferences hosted by the United Nations between 1992 and 1996. Focuses on recommendations or agreements made in key areas of particular importance to children and young people.